2007
DOI: 10.1161/strokeaha.107.485706
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Time-Domain Analysis of Cerebrovascular Autoregulation Using Near-Infrared Spectroscopy

Abstract: Background and Purpose-Assessment of autoregulation in the time domain is a promising monitoring method for actively optimizating cerebral perfusion pressure (CPP) in critically ill patients. The ability to detect loss of autoregulatory vasoreactivity to spontaneous fluctuations in CPP was tested with a new time-domain method that used near-infrared spectroscopic measurements of tissue oxyhemoglobin saturation in an infant animal model. Methods-Piglets were made progressively hypotensive over 4 to 5 hours by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
324
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 321 publications
(339 citation statements)
references
References 23 publications
13
324
1
1
Order By: Relevance
“…With hemodynamic impairment, as in unilateral carotid obstruction, these phases were significantly changed reflecting disturbed autoregulation. The correlation between changes in cerebral perfusion pressure and a cerebral tissue oxygenation index over time was demonstrated to correlate with cerebral autoregulation assessed using laser Doppler cortical blood flow during experimental intracranial hypotension in piglets [7]. A similar technique proved to be promising in neonates [8].…”
Section: Abpmentioning
confidence: 93%
See 1 more Smart Citation
“…With hemodynamic impairment, as in unilateral carotid obstruction, these phases were significantly changed reflecting disturbed autoregulation. The correlation between changes in cerebral perfusion pressure and a cerebral tissue oxygenation index over time was demonstrated to correlate with cerebral autoregulation assessed using laser Doppler cortical blood flow during experimental intracranial hypotension in piglets [7]. A similar technique proved to be promising in neonates [8].…”
Section: Abpmentioning
confidence: 93%
“…Using the same principle, a moving correlation coefficient between 10 s averages of ABP and TOI signals (Tox) was calculated. A similar index, using the INVOS TM cerebral oxymeter, was validated in piglets using laser Doppler flowmetry and cerebral perfusion pressure measurements during graded hypotension experiments [7]. Values from the right and left hemisphere from TCD and NIRS were averaged for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, THRT in prospective observational studies was shown to be useful in predicting clinical deterioration after SAH. 2,6 However, while clinical and experimental data exist supporting the validity of Sxa and TOxa, 13,23,25,31,32,34 neither index has been evaluated for its power to predict DCI. The mean flow index, Mx, which is derived from mean FV and CPP and its noninvasive version, Mxa, where ABP is used instead of CPP, have been previously investigated in patients with SAH.…”
Section: Methodsological Considerationsmentioning
confidence: 99%
“…(3) Near-infrared spectroscopy-based autoregulation, TOxa, was calculated as a moving, linear correlation coefficient between values of tissue oxygenation index and ABP from a 300-second window with an update every 10 seconds. [23][24][25] The minimum monitoring time required for results to be considered meaningful was 30 minutes.…”
Section: Calculation Of Hemodynamic Parametersmentioning
confidence: 99%
See 1 more Smart Citation